Physicochemical studies of a newly synthesized molecule, 6-methyl-3-phenethyl-3,4-dihydro-1H-quinazoline-2-thione (JSH18) for topical formulations - Kim, Sujin; Jung, Sang-Hun; Cho, Cheong-Weon (Archives of pharmacal research, 2008)
A new molecule having the structure of 6-methyl-3-phenethyl-3,4-dihydro-1H-quinazoline-2-thione (JSH18) was synthesized and possibly presupposed to show depigmentation through the inhibition of tyrosinase which is involved in formation of melanin. Therefore, we are going to develop JSH18 as an inhibitor of melanin synthesis with topical formulations to show its optimal efficiency for skin whitening based on preformulation studies. The preformulation to figure out the physicochemical properties was done by solubility measurements, differential scanning calorimetry study, scanning electron microscopy as well as cell viability assay and skin retention study. Through solubility test, glycofurol, N-methyl pyrrolidones, and isopropanol showed best solubilizing effects. JSH18 showed a strong single endothermic peak at 180.6°C and its millimeter-sized particles could be reduced by grinding suggesting the improvement of solubility. Interestingly, the cytotoxicity of JSH18 was different according to the cell origin type. JSH 18 showed the cell viability at the concentration of 4 uM in human keratinocyte HacaT cells but that was suddenly dropped at the concentration of 400 uM in murine keratinocyte PAM212 cells. Based on above preformulation results, formulation studies of JSH18 will be performed for the development of topical formulations in future.